Analyse De L'efficacité Technique Des Exploitations Agricoles Familiales À Maurice - Ndiaye, Malick (European Scientific Journal, ESJ, 2018)
This study was undertaken to determine the technical efficiency of family farms and to identify the factors which determine their productivity. All in all, 200 farmers were randomly selected and interviewed using a structured questionnaire to obtain data on agricultural production and input use during 2014. The Data Envelopment Analysis (DEA) technique was used to determine the levels of technical efficiency of such enterprises. Besides, a Tobit regression model was applied to identify the factors influencing the technical efficiency of farmers in agricultural production. The average technical efficiency under the variable scale yield is 0.726. This implies that it is possible to increase agricultural production by 27.4% compared to the current level of inputs. The results show that 46.5% of the sample is technically efficient under variable scale yield. The results showed that productivity is significantly influenced by the sex of the farmer, the area of cultivated land and the wage of labor. It is therefore recommended to undertake a policy to improve the formal education of producers, to build capacity of their organizations and facilitate to them access to land and inputs.